Can Aspartate Aminotransferase in the Cerebrospinal Fluid Be a Reliable Predictive Parameter? - Kelbich, Petr; Radovnický, Tomáš; Selke-Krulichová, Iva; Lodin, Jan; Matuchová, Inka; Sameš, Martin; Procházka, Jan; Krejsek, Jan; Hanuljaková, Eva; Hejčl, Aleš (Brain sciences, 2020)
Brain ischemia after central nervous system (CNS) bleeding significantly influences the final outcome of patients. Catalytic activities of aspartate aminotransferase (AST) in the cerebrospinal fluid (CSF) to detect brain ischemia were determined in this study. The principal aim of our study was to compare the dynamics of AST in 1956 CSF samples collected from 215 patients within a 3-week period after CNS hemorrhage. We compared concentrations of the AST catalytic activities in the CSF of two patient groups: survivors (Glasgow Outcome Score (GOS) 5-3) and patients in a vegetative state or dead (GOS 2-1). All statistical evaluations were performed using mixed models and the F-test adjusted by Kenward and Roger and the Bonferroni adjustment for multiple tests. The significantly higher catalytic activities of AST in the CSF from patients with the GOS of 2-1 when compared to those who survived (GOS 5-3, p = 0.001) were found immediately after CNS haemorrhage. In the further course of time, the difference even increased (p < 0.001). This study confirmed the key association between early signs of brain damage evidenced as an elevated AST activity and the prediction of the final patient's clinical outcome. The study showed that the level of AST in the CSF could be the relevant diagnostic biomarker of the presence and intensity of brain tissue damage.
Keywords: brain tissue injury; aspartate aminotransferase; CNS haemorrhage; cerebrospinal fluid